5thgeneration Wireless Network using Distributed Power Control, Novel and round Robin Scheduling Algorithms - Supriya, P.; Rao, Dr.S.P.V. Subba (International journal of recent technology and engineering, 2019)
The demand for higher networking quality i.e., 5G technology and improved wireless connectivity is increasing rapidly in emerging Cyber-Physical Systems (CPS). In this paper, we looked at the question of reducing total power transmission with power control and resource allocation in 5 G networks where there is mutual interference between cells using the distributed resource allocation algorithm, Packet Scheduling and compared with Round Robin Scheduling algorithm. Power control was indeed an efficient way to enhance wireless system ability. It was assumed that energy levels can be allocated from a constant spectrum in prior job on energy control. But energy levels are allocated from a discrete set in practice. In this work, we consider minimizing the complete transmitted energy over specified discrete sets of available energy levels subject to maintaining an acceptable quality of signal for each mobile. Our algorithm has reduced computational complexity compared to the current optimization algorithm, where each resource is assigned to a maximum of one user over a period of time. Numerical results verify our proposed algorithm's efficiency and convergence.